Barriers and facilitators to using vaporised nicotine products as smoking cessation aids among people receiving treatment for substance use disorder. (January 2022) - Lum, Alistair; Skelton, Eliza; Robinson, Maryanne; Guillaumier, Ashleigh; Wynne, Olivia; Gartner, Coral; Borland, Ron; Baker, Amanda; Dunlop, Adrian; Wilkinson, Ross B; Bonevski, Billie
Highlights: People in AOD treatment stated VNPs satisfy nicotine cravings and behavioral habits. VNPs should be easy to use, maintain and access to increase use to quit smoking. Further research on VNPs to quit smoking among people in AOD treatment is required. Abstract: Introduction: Vaporised nicotine products (VNPs) may be useful smoking cessation aids for people in alcohol and other drug (AOD) treatment, a population with high tobacco-related morbidity and mortality rates. This qualitative study aimed to examine the barriers and facilitators of using VNPs as part of a clinical trial to reduce or quit smoking among people in AOD treatment. Methods: Thirteen people in AOD treatment who were participating in a trial of VNPs for smoking cessation (QuitENDs) completed a brief semi-structured interview examining experiences of using VNPs to reduce or quit smoking. Transcribed data was analysed using the iterative categorisation framework. Results: Many participants expressed the benefit of having a smoking cessation aid that addressed nicotine cravings and the behavioural hand-to-mouth action to help them reduce or quit smoking. Although many participants reported that VNPs were easy to use, some found maintaining the device to be challenging. Some participants described Australian regulations limiting use of VNPs as reducing their desire to use the device as a cessation aid. Many participants attempting to reduce or quit tobacco and cannabis simultaneously stated that VNPs alone were insufficient to help them reduce or quit tobacco. Conclusions: VNPs hold significant promise as smoking cessation aids among people in AOD treatment because of their unique ability to satisfy both nicotine cravings and behavioural habits. However, multiple barriers, such as accessibility, maintenance, and the challenges of reducing other substance use simultaneously also need to be addressed for optimal engagement in clinical trials with VNPs to quit smoking.